Microfluidic synthesis of protein-loaded nanogels in a coaxial flow reactor using a design of experiments approach. Issue 7 (24th February 2021) - Whiteley, Zoe; Ho, Hei Ming Kenneth; Gan, Yee Xin; Panariello, Luca; Gkogkos, Georgios; Gavriilidis, Asterios; Craig, Duncan Q. M.
Abstract : A coaxial flow reactor is used to develop lysozyme-loaded nanogels, optimised via a design of experiments approach. Abstract : Ionic gelation is commonly used to generate nanogels but often results in poor control over size and polydispersity. In this work we present a novel approach to the continuous manufacture of protein-loaded chitosan nanogels using microfluidics whereby we demonstrate high control and uniformity of the product characteristics. Specifically, a coaxial flow reactor (CFR) was employed to control the synthesis of the nanogels, comprising an inner microcapillary of internal diameter (ID) 0.595 mm and a larger outer glass tube of ID 1.6 mm. The CFR successfully facilitated the ionic gelation process via chitosan and lysozyme flowing through the inner microcapillary, while cross-linkers sodium tripolyphosphate (TPP) and 1-ethyl-2-(3-dimethylaminopropyl)-carbodiimide (EDC) flowed through the larger outer tube. In conjunction with the CFR, a four-factor three-level face-centered central composite design (CCD) was used to ascertain the relationship between various factors involved in nanogel production and their responses. Specifically, four factors including chitosan concentration, TPP concentration, flow ratio and lysozyme concentration were investigated for their effects on three responses (size, polydispersity index (PDI) and encapsulation efficiency (% EE)). A desirability function was applied to identify the optimum parameters to formulate nanogels in the CFR with ideal characteristics. Nanogels prepared using the optimal parameters were successfully produced in the nanoparticle range at 84 ± 4 nm, showing a high encapsulation efficiency of 94.6 ± 2.9% and a high monodispersity of 0.26 ± 0.01. The lysis activity of the protein lysozyme was significantly enhanced in the nanogels at 157.6% in comparison to lysozyme alone. Overall, the study has demonstrated that the CFR is a viable method for the synthesis of functional nanogels containing bioactive molecules.